Relationship between personality traits and self-control in emergency nurses in western Iran - Safura safavi; Amir Jalali; MohammadJavad Veisimiankali; Nader Salari; Somayeh Fallah; Tayebeh Mahvar (Journal of Research Development in Nursing and Midwifery, 2025)
Background: Personality traits significantly influence professional and occupational behaviors, allowing for the prediction of specific actions in various work-related contexts. Additionally, these traits play a crucial role in the development of self-control. This study aimed to evaluate personality traits and their association with self-control among nurses working in the emergency departments (EDs) of hospitals. Methods: This cross-sectional study was conducted in Kermanshah, Western Iran, in 2022. The study sample comprised 154 nurses working in the EDs, selected using convenience sampling. Data were collected using the NEO Five-Factor Inventory and the Nikmanesh Self-Control Questionnaire. The data were analyzed using SPSS version 25, employing descriptive statistics, independent t-tests, ANOVA for group comparisons, and Pearson’s correlation, with a significance level set at 0.05. Results: The mean age of the participants was 33.5±6.2 years (range: 23 to 54). The findings showed that there was a significant correlation between the components of personality traits and restraint in nurses (P<0.001). Personality traits can explain restraint in nurses working in EDs. All subscales of restraint were also significantly correlated with negative personality traits, except impulsivity and risk-taking. Conclusion: The findings of this study suggest that personality traits significantly influence the self-control of nurses. Notably, stronger personality traits in all dimensions, except neuroticism, are inversely related to the self-control scores of nurses. Consequently, measures should be taken to improve the performance and job quality of nurses.